FACTORS CAUSING STRESS IN TYPE 2 DIABETES MELLITUS PATIENTS - Ayu Nursucita; Lina Handayani (Jambura Journal of Health Sciences and Research, 2021)
Diabetes mellitus is a dangerous disease caused by increased glucose levels, increased diabetes mellitus is caused by genetic factors, obesity, sudden lifestyle changes, wrong diet, non-compliance in taking medication, lack of exercise, age, smoking and stress. The purpose of this literature study is to discuss the factors that cause stress in people with diabetes mellitus type 2. The method used is a literature review study, the literature used is a National Journal published from 2011 to 2021. Literature was collected through the database https://garuda.ristekbrin.go.id/ and google scholar by using the search words "diabetes mellitus stress level type 2", "diabetes mellitus type 2 emotional disorder", and "diabetes mellitus type 2 stress causes". The search results obtained 100 articles, then after being filtered using inclusion and exclusion measuring techniques such as causes of stress in people with type 2 diabetes mellitus, 90 articles were removed, then 10 reviewed journal articles were obtained. The results of the review show the factors that cause stress levels in type 2 diabetes mellitus sufferers, namely due to the length of the treatment process, being required to change their lifestyle by implementing a strict diet every day, changes in physical form such as weight loss, duration of healing during wounds, and worry if complications occur.